The coopetition of human intelligence and artificial intelligence through the prism of irrationality - Marie-Noelle Albert; Salah Koubaa (Frontiers in Human Dynamics)
Artificial intelligence (AI) is sometimes seen as a threat to humans, posing both ethical challenges and job losses; sometimes, as an opportunity. The aim of this article, which is purely conceptual, is to understand the AI-Human Intelligence (HI) relationship from a cooperative, co-operative and competitive perspective, through the rationality-irrationality dialog between the two forms of intelligence. Humans can never be as rational as AI. Consequently, if it hides its irrational component, it could compete with AI, but in this game, humans are sure to lose. It is this irrationality (in permanent dialogue with rationality) that should be valued to enable human-machine coopetition.